Acute Toxicity Effect of The Ethanolic Extract of Watercress Herb (Nasturtium officinale R. Br.) in Mice - Herawaty Ginting; Aminah Dalimunthe; Julia Reveny (Indonesian Society for Cancer Chemoprevention, 2016)
Watercress (Nasturtium officinale R. Br.) is an annual plant of the Brasicaceae family. Watercress has efficacy in the treatment of a hypo-allergenic, anti-diabetic, antioxidant, anticancer, and treatment of tuberculosis.The purpose of this research was to determine the potential for acute toxicity of ethanolic extract of watercress. This study aims to observe the histopathology liver , kidney , heart mice and to determine the LD50. Test animals used were 40 male mice and 40 female mice were divided into 8 groups. Group 1 as the control group were given Na – CMC 0,5 % b/v and groups 2-8 were given ethanol extract of watercress herb with a doses of 0,5; 5; 50 ; 500 ; 1000 ; 2000; and 4000 mg/kg bw . LD50 test is determined by the number of deaths in the test group during the 14 days of treatment in the form of one administration of the test materials. Histopathological results at the highest doses showed necrosis and hydropic degeneration of the liver, serosis the kidneys, and the heart inflammation with myofibril irregular heart. LD50 test demonstrated the practical test material is not toxic because no test animals died.Keywords: acute toxicity, Nasturtium officinale R. Br., Ethanolic extract